Hellboy, Into the silent sea - Mignola, Mike; Gianni, Gary (Dark Horse Books, 2017)
"Hellboy sets sail from the wreckage of a deserted island only to cross paths with a ghost ship. Taken captive by the phantom crew that plans to sell him to the circus, Hellboy is dragged along by a captain who will stop at nothing in pursuit of a powerful sea creature"--